Subject as a legal category - Benio, Marek (Journal of Public Governance, 2014)
It is hard to imagine an academic debate on subjects and subjectivity in which there was no question of the legal meaning of these concepts. Subjectivity is a central notion in the civil law, but it is also important for other branches of law: criminal, administrative, and international. When and how does a being become a subject of law? Does he or she do it by acquiring rights, or perhaps the other way round: there is no right on its own, without its subject. These theoretical questions have very practical implications, e.g. in rights of succession. But they will become more and more important when it comes to subjectivity of human clones and the development of artificial intelligence. Once futurist illusions of fiction writers have become a reality that calls for regulation. Another important thread of thought presented in the paper is how and on what ground global entities (corporations, organizations) become legal subjects with “global” rights.